Treatment persistence during therapeutic sequences with adalimumab and infliximab in the treatment of Crohn's disease - Carlos Taxonera; Pilar Robledo; Antonio Rodríguez (Revista Espanola de Enfermedades Digestivas)
Background and aim: Tumor necrosis factor (TNF) inhibitors have demonstrated efficacy and safety in the treatment Crohn's disease (CD). However, the loss of response over time means that they are usually used sequentially. The aim of this study was to compare treatment persistence with different sequences of TNF inhibitors in patients with active luminal CD. Methods: A Markov model (3-month cycles) was developed to simulate the therapeutic sequences of beginning biological treatment with infliximab or adalimumab, with a time horizon of three years. Each state of the model represented treatment (induction, standard dose or escalated dose) with each TNF inhibitor or the state without biological treatment. The transition probabilities between states were determined by the clinical response to TNF inhibitors obtained from the literature. The likelihood of discontinuation due to adverse effects was also considered. Results: After three years, the percentage of CD patients receiving infliximab and adalimumab as a first TNF inhibitor that remained in treatment was 52.8% and 59.3% (p = 0.1) respectively. Median time to discontinuation of the standard dose was 26.26 months in patients who started with adalimumab and 24.39 months in patients who started with infliximab. Conclusion: In the model, there were no significant differences in persistence after three years with the initial drug among patients with active luminal CD starting treatment with infliximab or adalimumab.